Bacterial Microcompartment-Dependent 1,2-Propanediol Utilization of Propionibacterium freudenreichii - Dank, Alexander; Zeng, Zhe; Boeren, Sjef; Notebaart, Richard A.; Smid, Eddy J.; Abee, Tjakko (Frontiers in Microbiology, 2021)
Bacterial microcompartments (BMCs) are proteinaceous prokaryotic organelles that enable the utilization of substrates such as 1,2-propanediol and ethanolamine. BMCs are mostly linked to the survival of particular pathogenic bacteria by providing a growth advantage through utilization of 1,2-propanediol and ethanolamine which are abundantly present in the human gut. Although a 1,2-propanediol utilization cluster was found in the probiotic bacterium Propionibacterium freudenreichii, BMC-mediated metabolism of 1,2-propanediol has not been demonstrated experimentally in P. freudenreichii. In this study we show that Propionibacterium freudenreichii DSM 20271 metabolizes 1,2-propanediol in anaerobic conditions to propionate and 1-propanol. Furthermore, 1,2-propanediol induced the formation of bacterial microcompartments, which were visualized by transmission electron microscopy and resembled BMCs found in other bacteria. Proteomic analysis of 1,2-propanediol grown cells compared to L-lactate grown cells showed significant upregulation of proteins involved in propanediol-utilization (pdu-cluster), DNA repair mechanisms and BMC shell proteins while proteins involved in oxidative phosphorylation were downregulated. 1,2-Propanediol utilizing cells actively produced vitamin B12 (cobalamin) in similar amounts as cells growing on L-lactate. The ability to metabolize 1,2-propanediol may have implications for human gut colonization and modulation, and can potentially aid in delivering propionate and vitamin B¬12 in situ.